Experiment Design Effects of Cooling Media Variations Toward Strictness and Pulling Strenghness of Materials of ST 41 in Heat Treatment Process - Sumiati; Verayanti, Fransisca Diah Ayu; Purwati (Nusantara Science and Technology Proceedings)
Steel of ST 41 is the steel be classified as low carbon steel with guide compositions about 0.37-0.43%C, 0.5-0.35%Si, 0.60-0.90%Mn. The steel sometimes has the unfit characteristic to the need, so It needs another treatment to change characteristic and structure from steel of ST 41 itself be changed in heat treatment methods. Cooling media can affect the strictness characteristics of steel of ST 41. The heating process in the research uses 723oC withholding in an hour. Then it is cooled quickly in many Cooling media. Cooling media be used in the research are water, salt, and coconut oil by using holding time on each Cooling media in 5 to 20 minutes. After done in Quenching process, the steel of ST 41 is done strictness tests and strengths tests to use Rockwell method tests and analyzed. This research result will recommend on general formulation to predict in strictness of steel of ST 41, if it use two co positions namely: Y= 97.2118+0.0983*x-0.4223*y 0.0114*x*x+0.0026*x*y+0.0023 *y*y. can predict pulling strength ness of ST 41 material, For a while if they use two compositions namely Y = 46.7828+0.3293*x+0.2271*y-0.0132*x*x-1.1689E-14*x*y-0.0009*y*y. so each x1 and x2 areas holding time and temperature.